Study of sustainability status of the implementation of ISPO (Indonesian Sustainable Palm Oil) in plasma farmers oil palm plantation. Issue 1 (March 2021) - Rosyani; Edison; Ulma, Riri; Aziz, Muhammad
Abstract: ISPO (Indonesia Sustainable Palm Oil) is a mandatory certification policy issued by the Indonesian government. ISPO is aimed at private oil palm plantation businesses and smallholder groups. Plasma farmers are farmers who partner with companies. It is appropriate for ISPO certified companies, and smallholders will be the same in implementing ISPO. This study aims to determine the role of companies in plasma farmers in implementing the ISPO principles for plasma farmers, then to find out the implementation of the ISPO principles by plasma smallholders and to analyze the sustainability status of the implementation of the ISPO principles carried out by plasma farmers. The study used the RAP-Palm method and sampling of plasma farmers in three companies in the West, East, and Central regions of Jambi Province. The results showed that companies that have received ISPO certificates have not been optimal for plasma farmers in applying the ISPO principles. Companies that partner with plasma farmers have not encouraged plasma farmers to implement the ISPO principles. At the same time, the plasma smallholders have not optimally applied the ISPO principles. The MDS analysis results showed that the plasma farmers' sustainability status in implementing the principles is in the medium category (56, 02). A new regulation is recommended that encourages companies to help empower plasma farmers in implementing ISPO principles and needs to empower the knowledge and education of smallholders in implementing the ISPO principle. As well as rewards for plasma farmers who implemented ISPO to get a premium price.